Exploration of the impact of green supply chain management practices on manufacturing firms’ performance through a mediated-moderated model - Zhaolei, Li; Nazir, Samera; Hussain, Iftikhar; Mehmood, Saqib; Nazir, Zarish (Frontiers in Environmental Science, 2023)
This study aimed to examine the impact of green supply chain management (GSCM) practices on the performance of manufacturing firms. It explored the mediating role of green innovation (GI) and the moderating role of information sharing (IS) and information technology innovation (ITI) on the relationship between GSCM practices and manufacturing firms' performance. Data were collected through a structured questionnaire from employees working in manufacturing firms in Pakistan. Random sampling was used to select the participants. The hypotheses were tested using partial least squares (PLS) analysis. The study revealed that GSCM practices significantly positively impacted manufacturing firms' performance. It highlighted the mediating role of green innovation, suggesting that GSCM practices fostered innovation and improved firm performance. The study also uncovered the moderating role of information sharing and IT innovation, indicating that the effectiveness of GSCM practices in driving performance varied based on the extent of information sharing and IT innovation within the industry. The findings of this study had practical implications for industry practitioners and policymakers. Implementing effective GSCM practices and promoting green innovation could enhance firm performance in the manufacturing sector. Recognizing the importance of information sharing and IT innovation was crucial, as they significantly enhanced the effectiveness and efficiency of GSCM practices. This study contributed to the existing literature by examining the relationships among GSCM practices, green innovation, information sharing, IT innovation, and manufacturing firm performance. It provided insights into the mechanisms through which GSCM practices impacted firm performance, offering a comprehensive understanding of the role of green innovation and the moderating effects of information sharing and IT innovation.